CSF sulfatide distinguishes between normal pressure hydrocephalus and subcortical arteriosclerotic encephalopathy. Issue 1 (1st July 2000) - Tullberg, M; Månsson, J-E; Fredman, P; Lekman, A; Blennow, K; Ekman, R; Rosengren, L E; Tisell, M; Wikkelsø, C
Abstract : OBJECTIVES: To examine the CSF concentrations of molecules reflecting demyelination, neuronal and axonal degeneration, gliosis, monoaminergic neuronal function, and aminergic and peptidergic neurotransmission in a large series of patients with normal pressure hydrocephalus (NPH) or subcortical arteriosclerotic encephalopathy (SAE), to elucidate pathogenic, diagnostic, and prognostic features. METHODS: CSF concentrations of glycosphingolipid (sulfatide), proteins (neurofilament triplet protein (NFL), glial fibrillary acidic protein (GFAP)), neuropeptides (vasoactive intestinal peptide (VIP), 4-aminobutyric acid (GABA)), and monoamines (homovanillic acid (HVA), 5-hydroxy-indoleacetic acid (5-HIAA), 4-hydroxy-3-methoxyphenylglycol (HMPG)) were analysed in 43 patients with NPH and 19 patients with SAE. The diagnoses of NPH and SAE were based on strict criteria and patients with NPH were subsequently operated on. Twelve clinical variables, psychometric tests measuring perceptual speed, accuracy, learning, and memory and a psychiatric evaluation were performed in all patients and before and after a shunt operation in patients with NPH. RESULTS: The CSF sulfatide concentration was markedly increased in patients with SAE (mean 766, range 300–3800 nmol/l) compared with patients with NPH (mean 206, range 50–400 nmol/l) (p<0.001). 5-HIAA, GABA, and VIP in CSF were higher in patients with SAE than in patients with NPH. The patients with NPH with cerebrovascular aetiology had higher sulfatide concentrations and a poorer outcome after shunt surgery than patients with NPH with other aetiologies. CONCLUSIONS: The pathogenesis of the white matter changes in NPH and SAE is different and ischaemic white matter changes can be a part of the NPH state. The markedly increased CSF sulfatide concentrations in patients with SAE indicate ongoing demyelination as an important pathophysiological feature of SAE. The CSF sulfatide concentration distinguished between patients with SAE and those with NPH with a sensitivity of 74% and a specificity of 94%, making it an important diagnostic marker.